Cognitive Diversity on Team Innovation During the Covid-19 Pandemic: Do We Need An Intrinsic Motivation as A Mediator? - Devi Yulia Rahmi; Fatma Poni Mardiah; Ratni Prima Lita (Universitas Teknologi Yogyakarta, 2023)
This research aims to analyze the impact of cognitive diversity on intrinsic motivation, cognitive diversity on team innovation, and the impact of intrinsic motivation, as a mediator, on cognitive diversity and team innovation. This research applied an explanatory approach to hypothesis testing. We conducted a survey in which 107 questionnaires were distributed to 33 work teams in the furniture industry in West Sumatra, Indonesia. Findings indicate that cognitive diversity had a significant positive impact on team innovation. Contrastively, cognitive diversity did not have any effect on intrinsic motivation. Besides, we also figured out that intrinsic motivation was not a mediator between cognitive diversity and team innovation. Findings indicate that cognitive diversity had a significant positive impact on team innovation. Contrastively, cognitive diversity did not have any effect on intrinsic motivation. Besides, we also figured out that intrinsic motivation was not a mediator between cognitive diversity and team innovation. The study provides a comprehensive understanding of knowledge sharing and team climate on the relationship between cognitive diversity and team innovation, missing in previous empirical studies. Then, the study is relevant because of inconclusive findings from past studies examining the relationship between cognitive diversity and team innovation.